Influence of thermal denaturation on whey protein isolates in combination with chitosan for fabricating Pickering emulsions: a comparison study - Pu, Yilin; Long, Yuxiang; Xu, Die; Niu, Yongkang; Wu, Qinglong; Chen, Shiyu; Wang, Ruozhen; Ge, Ruihong (Frontiers in Nutrition, 2024)
Composite natural emulsifiers such as whey protein isolate (WPI) and chitosan (CS) are commonly used in Pickering emulsions to address the effect of thermal deformation of proteins before complexation with CS and heating after complexation. In this study, the properties of WPI and CS composites were investigated by complexing CS with either unmodified WPI or thermally denatured WPI (DWPI). Three types of composite particles were prepared, WPI-CS, DWPI-CS, and D(WPI-CS). Atomic force microscopy revealed that the composite particles formed larger aggregates with increased contour size and surface roughness compared to CS and WPI, whereas the interfacial tension decreased, indicating improved emulsifying abilities. Fourier-transform infrared analysis revealed differences in the hydrogen bonds between CS and WPI/DWPI. All three composite particles formed stable emulsions with droplet sizes of 20.00 ± 0.15, 27.80 ± 0.35, and 16.77 ± 0.51 μm, respectively. Thermal stability experiments revealed that the curcumin emulsion stabilized with WPI-CS and DWPI-CS exhibited relatively better thermal stability than that stabilized with D(WPI-CS). In vitro experiments results indicated that the bioaccessibility of the curcumin emulsion stabilized with WPI-CS was 61.18 ± 0.16%, significantly higher than that of the emulsions prepared with the other two composite particles (p ˂ 0.05). This study will enable the customized design of WPI composite-based Pickering emulsions for application in the food and nutrition industries.